1996
DOI: 10.1097/00004836-199606000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Early or Delayed Endoscopy for Patients with Peptic Ulcer Bleeding

Abstract: The benefit of early endoscopy in the management of peptic ulcer bleeding remains controversial. In this study we looked at the role of early endoscopy in bleeding peptic ulcer patients with clear, "coffee grounds," or bloody nasogastric aspirate. A consecutive series of 325 patients with peptic ulcer bleeding were included (218 patients with clear aspirate, 77 patients with coffee-grounds aspirate, and 30 patients with bloody aspirate). They were randomized to receive early endoscopy (within 12 h of arrival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 22 publications
4
99
1
8
Order By: Relevance
“…However, whether a bloody aspirate provides better prognostic information than other readily available data such as blood pressure and pulse is not known. In a prospective trial in 325 patients, the proportion with " shock " (systolic blood pressure < 100 mm Hg and pulse > 100 beats / minute) correlated with the NG aspirate fi nding: 11 % with a clear aspirate, 36 % with coff ee-grounds, and 60 % with bloody aspirate ( 28 ).…”
Section: Prognostic Valuementioning
confidence: 99%
“…However, whether a bloody aspirate provides better prognostic information than other readily available data such as blood pressure and pulse is not known. In a prospective trial in 325 patients, the proportion with " shock " (systolic blood pressure < 100 mm Hg and pulse > 100 beats / minute) correlated with the NG aspirate fi nding: 11 % with a clear aspirate, 36 % with coff ee-grounds, and 60 % with bloody aspirate ( 28 ).…”
Section: Prognostic Valuementioning
confidence: 99%
“…Other studies have shown that combined pharmacological and endoscopie treatment is superior to endoscopie treatment alone, but does not increase the 15-day survival in variceal bleeding [18,19]. Furthermore, the same critisisms apply to all prospective trials of ulcer bleeding which attempt to address strategies for diagnostic and therapeutic endoscopy [5,6]. A study of patients with ail types of upper gastrointestinal bleeding needs to be done in order to address the question of the overall value of EEE.…”
Section: Outcome According To Where the Endoscopy Was Canied Outmentioning
confidence: 99%
“…It favorably affects recurrent bleeding, the need for surgery, and, probably, survival [1][2][3][4]. The question of whether endoscopie hemostasis should be performed early after hospital admission has also been examined in randomized trials [5,6], in observational cohort studies [7][8][9], and in a systematic review [10], and these papers have described early endoscopy as advantageous. However, it is difficult the Baylor bleeding score and the Rockall score), and differed only in the treatment they received.…”
mentioning
confidence: 99%
“…The majority of data published suggest that early endoscopy (generally defined as endoscopy within 24 hours) is safe and can reduce transfusion requirements and length of hospital admission.12 However, no mortality benefit could be identified with early endoscopy. Several studies have investigated the efficacy of urgent endoscopy (endoscopy performed with 6 or 12 hours) compared with elective endoscopy [3][4][5]. The results of these studies suggest that urgent endoscopy can reduce hospital stay and amount of blood transfusion.…”
Section: Discussionmentioning
confidence: 99%